Examination of the Use of Nielsen's 10 Usability Heuristics & Outlooks for the Future. (September 2017) - Gonzalez-Holland, Emily; Whitmer, Daphne; Moralez, Larry; Mouloua, Mustapha
Heuristics are commonly employed throughout various stages of the design process to evaluate the usability of interfaces. Heuristic Evaluation (HE) provides researchers with a cost effective and practical means to effectively assess designs. In this article, we aim to outline the development and application of one of the most frequently cited set of heuristic evaluation tools, Nielsen's (1994) 10 usability heuristics. Nielsen's heuristics have not only been applied to various modalities of interface design, but have also been compared to other usability evaluation methods. Moreover, in many cases they have been modified so that they can be applied in an ever-changing socio-technical environment. In reviewing these developments, we propose theoretical and practical implications of these heuristic methods and present an outlook for the future. We argue that with the rapid expansion and growth of technology in the last 20 years, Nielsen's 10 usability heuristics may need an update to remain consistent with modern usability problems.